THE SPECIAL FEATURES OF CULTURAL-VALUE ORIENTATIONS CLASSIFICATION - Rybak, Oksana (PSYCHOLOGICAL JOURNAL, 2017)
The article is dedicated to a problem of analysis of cultural-value orientations clusters. It puts together main and the most actual scientific classifications of cultural-value orientations and shows how value orientation shows individual hierarchy of preferences. In the article the clusters of cultural-value orientations are determined and analyzed. The cluster of reference towards human nature considers human nature good, evil, mixed and neutral, and also if is it changeable or not through whole life. The cluster of reference towards nature is created in the context of mastery, submission or harmony with nature. The domination in the culture hierarchical, equal or individual relations shows the cluster of attitude toward other people. In the cluster of attitude toward time past present and future orientations are distinguished. And the last dimension of human activity identifies being, being in becoming and doing categories of activity. The influence of cultural-value orientations on solving human problems is investigated. The problems are common to all peoples but there are different methods of decisions in different historical periods and different cultures. In this research scientific and practical value of studying culture-value orientations in different spheres of international business, cross-cultural psychology, child developing, international affairs, and sociology is showed. Perspectives of future researches of the problem are described.